Implementação de medidor de energia elétrica com arduino - CUNHA, Carlos Wellington Sousa da (2025)
This work proposes the development of an electrical energy meter capable of collecting electrical information specifically, voltage and current, instantly and simply, using a free hardware platform - Arduino as a base. Algorithms are run to calculate the energy consumption of a given load, the data is processed and the results are shown on an LCD display for local viewing. The main objective of this implementation is to facilitate the monitoring of residential electricity consumption, so that the consumer has a tool to monitor their expenses. The obtained results demonstrate that the developed prototype presents precision and simplicity compatible with experiments with didactic purposes.